The impact of ethical leadership on educational innovation in Chinese universities: The mediating role of faculty trust - YaLi, Ma; Zainol, Zuraidah (Journal of Islamic, Social, Economics and Development, 2026)
China's "Double First-Class" initiative has established educational innovation as a strategic priority for universities. Although various leadership styles have been examined in existing research, the specific function of ethical leadership requires further investigation. This research analyses how ethical leadership influences educational innovation within Chinese universities, with particular attention to the mediating role of faculty trust. The study gathered survey responses from 328 faculty members across multiple Chinese public universities. Through structural equation modelling, the findings demonstrate that ethical leadership not only directly promotes educational innovation but also operates through a complete mediating mechanism involving faculty trust. These results indicate that ethical leaders foster organisational trust, which, in turn, serves as a critical pathway to enabling innovation.